The freemason's daughter - Sackier, Shelley (HarperTeen, an imprint of HarperCollins Publishers, 2017)
When her clan is hired to build a garrison on the Duke's estate, Jenna ventures into dangerous territory in England and struggles with her growing attraction to her employer's son, who makes her question her family's mutinous secrets.